Mapeamento das voçorocas e análise da susceptibilidade erosiva no município de Uberlândia, MG - Pereira, Juliana Sousa (2021)
The gullies are permanent features in the landscape and responsible for the expressive contribution of sediments in the river channels, at the base of the slopes and in the reservoirs for water exploration. Regardless of the anthropic action, these processes of disintegration and transport comprise the natural dynamics of slope morphogenesis. However, the notion of impact and degradation is based on the intensity of action of these processes against land use and the resilience of the environments. Considering this issue, this work presents a study on soil erosion by gullies in the municipality of Uberlândia - Minas Gerais. The aim was to understand how research focused on this topic has been developed in different Brazilian graduate programs, mapping the erosive features established, identify the influencing conditions and analyze the municipality's susceptibility to rainfall erosion. In order to achieve these objectives, the theoretical foundation was carried out, the characterization of the study area, the use of bibliometric techniques, the application of visual interpretation techniques in the images of Google Earth and the multicriteria analysis together with the algebra of maps for the characterization of the degrees of erosive susceptibility. The integration of conditions that interfere with soil erosion in a GIS environment allowed the attribution of weights and the elaboration of a Susceptibility Map to gullies, which was validated by the occurrences of these features identified in the study area. Medium susceptibility classes are predominant comprising 61.21% of the compartment area associated with low slopes, low relief dissection rates, established in basaltic terrains and characterized by Red Nitosols, Red Latosols and Red-Yellow Latosols. The classes of high (26.12%) and very high (0.27%) susceptibility are mostly inserted in the geomorphological units of the Canyon do Rio Araguari and Planalto Dissecado do Tijuco according to their physiographic characteristics. The urban perimeter also presented a very high susceptibility, referring to the need to establish urban planning and territorial planning tools with a view to reducing the damage caused by gullies. Actions aimed at mitigating and managing watersheds in both rural and urban areas also need greater effectiveness, especially with regard to land use and occupation.